2015
DOI: 10.1111/inr.12178
|View full text |Cite
|
Sign up to set email alerts
|

Promotion or marketing of the nursing profession by nurses

Abstract: A three-level (individual, organizational and national) nursing marketing programme is proposed for implementation by nurse leadership and policy makers. Among proposed steps to improve marketing of the nursing profession are promotion of the image of nursing by the individual nurse in the course of her or his daily activities, formulation and implementation of policies and programmes to promote the image of nursing at the organizational level and drawing up of a long-term programme for promoting or marketing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 32 publications
(44 reference statements)
5
27
2
Order By: Relevance
“…The personal score of job satisfaction was represented by the mean. The original version's Cronbach's alpha was 0.91–0.92 (Meir & Yaari, ) and 0.89 (Kagan et al, ), while in the current study it was 0.90.…”
Section: Methodscontrasting
confidence: 53%
“…The personal score of job satisfaction was represented by the mean. The original version's Cronbach's alpha was 0.91–0.92 (Meir & Yaari, ) and 0.89 (Kagan et al, ), while in the current study it was 0.90.…”
Section: Methodscontrasting
confidence: 53%
“…Evidences showed that public image of nurses is not appropriate but diverse. [51] This can to some extent be a result of nurses' self-created image because they are not visible enough nor have enough discourse in public. [52] This self-concept and professional identity is driven from nurses' public image, work place, work values, education, and social and cultural values.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses typically are not inclined to promote their profession to the public or to other health workers or to agitate for policy changes. Researchers have proposed promoting the image of nursing by individual nurses in the course of their daily activities (Kagan et al 2015). On the other hand, nursing institutions could provide more platforms to help young people better understand the nursing profession (Wu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have proposed promoting the image of nursing by individual nurses in the course of their daily activities (Kagan et al. ). On the other hand, nursing institutions could provide more platforms to help young people better understand the nursing profession (Wu et al.…”
Section: Introductionmentioning
confidence: 99%